Causes of change in nitrophytic and oligotrophic lichen species in a Mediterranean climate: impact of land cover and atmospheric pollutants. (Environmental pollution (Barking, Essex : 1987), 2008)
With the aim of determining the main drivers of changes in nitrophytic and oligotrophic macro-lichen communities in an industrial region with a Mediterranean climate, we considered both land-cover types and atmospheric pollutants. We determined the relation between the abundance of nitrophytic and oligotrophic species with environmental factors considering the distance of influence of land-cover types. The results showed that oligotrophic species decreased in the proximity of artificial areas, barren land and agricultural areas, associated with higher concentrations of NO2 and Zn, and Ti, probably dust of industrial and agricultural origin. Nitrophytic species were positively related to all the mentioned land-cover types, and with higher concentrations of Fe and N. Magnesium, probably from ocean aerosols, was negatively related to oligotrophic species and positively to nitrophytic.